Diseño de un manual de procesos y procedimientos para alborautos sas Sede Tunja (2022)
The company ALBORAUTOS SAS dedicated to the purchase and sale of vehicles and spare parts for cars, constantly seeks leadership in the automotive market, always with a responsible attitude and generating brand loyalty, however, the functions of each one is not currently documented. of the members of the entity's team and the new personnel do not have a guide that facilitates the induction to their positions, a situation that causes inconveniences in the development of the processes such as omitting secondary functions, carrying out tasks that do not correspond to the assigned position and incomplete tasks.